New work situations call for familiar work design methods: Effects of task rotation and how they are mediated in a technology-supported workplace - Mlekus, Lisa; Lehmann, Janine; Maier, Günter W. (Frontiers in Psychology, 2022)
New digital assistive technologies strive to alleviate the completion of work tasks but thereby often threaten to make jobs increasingly monotonous. To counteract jobs becoming more and more monotonous, task rotation might be an appropriate technology feature. However, it is uncertain whether task rotation has unique positive effects, why it works, and whether there are any boundary conditions. To investigate this, we conducted two experimental vignette studies. In Study 1 (N1 = 135), we drew on the job characteristics model and self-determination theory to examine perceived task variety, skill variety, and task identity, and expected satisfaction of the need for competence as mediators of the effect of task rotation on anticipated employee attitudes (job satisfaction, intrinsic work motivation), behavior (subjective performance), and well-being (positive and negative affect). The investigated vignette described a job where a digital assistance system either indicated the task rotation or only supported work steps. Regression analyses showed direct effects of task rotation on expected job satisfaction, intrinsic motivation, and positive affect. There were indirect effects of task rotation on all outcomes except expected negative affect. We used Study 2 (N2 = 159) as an exact replication of Study 1. Additionally, to investigate the boundary conditions of task rotation effects, we drew on person-job fit theory and investigated openness to experience as a moderator of the effects of task and skill variety on the outcomes. Regression analyses showed direct effects of task rotation on expected job satisfaction, subjective performance, and positive affect. There were indirect effects of task rotation on all outcomes except expected negative affect and intrinsic motivation. Thus, the results of Study 1 could only be partly replicated. Openness to experience did not moderate the effects of task and skill variety on the outcomes. The results support the relevance of task rotation as a technology feature and indicate that rotations should offer especially skill variety and task identity, as these were the strongest mediators in our studies.